Sandwich‐Structured Fluorinated Polyimide Aerogel/Paraffin Phase‐Change Composites Simultaneously Enables Gradient Thermal Protection and Electromagnetic Wave Transmission - Tao Shi; Jianwei Jing; Zhiqiang Qian; Gaojie Wu; Guofeng Tian; Huan Liu; Xiaodong Wang (Advanced Science)
Abstract There is an emerging requirement of advanced functional materials for simultaneous thermal protection and electromagnetic wave‐transparent transmission applications. A novel polyimide (PI) aerogel‐based sandwich‐structural composite is developed to meet such a requirement in this study. This composite is based on a unidirectional fluorinated PI (FPI) aerogel as a lower layer, a nondirectional conventional PI aerogel as a middle layer, and a nondirectional FPI aerogel/paraffin phase‐change composite as an upper layer. The lower layer exhibits a unique unidirectional porous microstructure and an ultralow dielectric constant of 1.04. The upper layer possesses a dynamical temperature regulation capability thanks to its loaded paraffin having a high latent heat capacity of 242.7 J g−1. The presence of the nondirectional PI aerogel middle layer can effectively prevent against the leakage of paraffin from the upper layer to the surface of the composite. Through a rational integration of three functional layers, the developed sandwich‐structured composite not only can provide gradient thermal protection for hot objects over a long period but also exhibits an excellent wave‐transparent capability to establish communication between two electromagnetically shielded electronic devices. With such prominent thermal insulation and wave‐transparent functions, the sandwich‐structured composite exhibits great potential for specific applications in aircraft, spacecraft, radar systems, and satellite communication.